2001
DOI: 10.1053/ejvs.2001.1311
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Audit of Complex Wound and Graft Infections in Great Britain and Ireland: the Emergence of MRSA

Abstract: in this audit, MRSA was the commonest single organism cultured in patients with complex wound and graft infections after vascular surgery. This represents a major change in the spectrum of causative organisms relative to other, older published series. MRSA infections contribute towards an increased risk of adverse outcome and prolonged hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 9 publications
2
69
0
7
Order By: Relevance
“…Santos et al (1997) Naylor et al (2001), Staphylococcus foi isolado com maior frequência em cirurgias com menor grau de contaminação, como as limpas.…”
Section: Discussionunclassified
“…Santos et al (1997) Naylor et al (2001), Staphylococcus foi isolado com maior frequência em cirurgias com menor grau de contaminação, como as limpas.…”
Section: Discussionunclassified
“…18 There has been much debate on how to tackle the problem. In addition to infection control of outbreaks, screening to rule out MRSA colonisation also needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the SENTRY antimicrobial surveillance program reported that 36.8% of S. aureus isolates ribotyped belonged to multidrug-resistant, oxacillinresistant S. aureus strains (7). In Ireland, Naylor et al (23) found that MRSA was the commonest single organism cultured from patients with complex wound and graft infections after vascular surgery. In addition, the latest data from the European Antimicrobial Resistance Surveillance System showed an increase in MRSA from 39% in 1999 to 45% in 2002 in Ireland (37).…”
mentioning
confidence: 99%